Lightning Protection On Photovoltaic Systems: A Review On Current And Recommended Practices - N.I.Ahmad; M.Z.A.Ab-Kadir; M.Izadi; N.Azis; M.A.M.Radzi; N.H.Zaini; M.S.M.Nasir (Science Direct (Elsevier), 2024)
Renewable and Sustainable Energy Reviews Volume 82, Part 1, February 2018, Pages 1611-1619